Detection and Diversity evaluation of tetracycline resistance genes in grassland-based production systems in Colombia, South America - Santamaría, Johanna; López, Liliana; Soto, Carlos Y. (Frontiers in Microbiology, 2011)
Grassland-based production systems use approximately 26 percent of land surface on earth. However, there are no evaluations of these systems as a source of antibiotic pollution. This study was conducted to evaluate the presence, diversity, and distribution of tetracycline resistance genes in the grasslands of the Colombian Andes, where administration of antibiotics to animals is limited to treat disease and growth promoters are not included in animals’ diet. Animal (ruminal fluid and feces) and environmental (soil and water) samples were collected from six different dairy cattle farms and evaluated by PCR for the genes encoding ribosomal protection proteins (RPPs) tet(M), tet(O), tetB(P), tet(Q) tet(W), tet(S), tet(T), tet(A), and tetracycline efflux pumps tet(A), tet(B), tet(D), tet(H), tet(J), tet(Z), and tet(D). A wide distribution and high frequency for genes tet(W) and tet(Q) were found in both sample types. Other genes encoding RPPs ( tetB(P), tet(O), tet(M), tet(S) and tet(T)) were detected at lower frequencies and more restricted distributions. Genes encoding efflux pumps were not common in this region, and only two of them, tet(B) and tet(Z), were detected. DGGE-PCR followed by comparative sequence analysis of tet(W) and tet(Q) showed that the sequences detected in animals did not differ from those coming from soil and water, suggesting the transmission of tet genes from animal reservoirs to the environment. Additionally, there seems to be a differential flow of tet genes from one reservoir to the other because gene tet(O) and tetB(P), detected in high frequencies in feces, were detected in low frequencies or not detected at all in the environment. Finally, the farms sampled in this study showed more than 50% similarity in relation to the tet genes detected and their frequencies. However, farms closer in space and under the influence of the same hydrographic network were significantly more similar to each other.